Protein-ligand interactions of arylamine N-acetyltransferase from Mycobacterium smegmatis - Brooke, E (2003)
﻿ Tuberculosis is the world's largest cause of death from an infectious agent. Treatment is by an extended period of combination chemotherapy. Drug resistance is an increasing problem in tuberculosis therapy, particularly to the frontline anti-tubercular drug isoniazid (INH). Recombinant arylamine N-acetyltransferase (NAT) of Mycobacterium tuberculosis N-acetylates INH using the cofactor Acetyl Coenzyme A. NAT from M. tuberculosis is a polymorphic enzyme and also acetylates INH in vivo. Acetylated INH is inactive therapeutically against M. tuberculosis both in vivo and in vitro. The acetylation of isoniazid in the mycobacterial cell may compete with the activation of INH by the catalase-peroxidase, katG, and hence contribute to INH resistance in clinical isolates. Inhibition of NAT in M. tuberculosis may thus increase the efficacy of INH therapy. A novel assay based around the detection of free Coenzyme A released during the acetylation reaction was used to determine the substrate specificity of recombinant NAT from the related Mycobacterium M. smegmatis (MSNAT). A relationship was observed between the lipophilicity of simple arylamine substrates and the rate of acetylation by MSNAT. Several MSNAT substrates possess antibacterial activity. The assay could also be used to screen compound libraries for MSNAT inhibitors. Synthesis of seventeen thiazolidinedione sultams in collaboration with Dr.Vickers (Dyson Perrins), identified as weak inhibitors of MSNAT, gave a minimum competitive inhibitory constant of 14μM. Screening a library of 5,074 drug-like compounds for inhibition of MSNAT identified thirteen compounds with semi-maximal inhibition constants (IC50) of below 10μM. Based on this, fifteen maleimides were synthesised and were irreversible inhibitors of MSNAT with submicromolar potency. Similarly, ninety-six aminothiazoles were synthesised by Dr. Vickers and were uncompetitive inhibitors of MSNAT with a minimum IC50 of 1.5μM. The most potent aminothiazole showed no effect on the growth of M. smegmatis or M. bovis BCG or the sensitivity of the bacteria to isoniazid. However the aminothiazoles were shown not to penetrate the cells.